P04.64 Molecular characterization of glioma patient derived orthotopic xenografts to improve outcome of preclinical studies. (19th September 2018) - Golebiewska, A; Hau, A; Oudin, A; Houben, L; Stieber, D; Azuaje, F; Kaony, T; Muller, A; Hertel, F; Mittelbronn, M; Bjerkvig, R; Niclou, S P
Abstract: Background: It is well recognized that long term cell cultures are poor models to study human cancer, largely because of loss of clonal heterogeneity, accumulation or loss of genomic alterations and adaptation to a highly artificial environment. Patient-derived orthotopic xenografts (PDOX) based on organotypic three-dimensional tumor spheroids from human glioma samples are proposed to represent a reliable and clinically-relevant animal model. Methods: A living biobank of PDOX models from 34 glioma patients (grade III and IV), including longitudinal patient samples with matched recurrent tumors, were generated by intracranial grafting of organotypic tumor spheroids in immunedeficient mice. Genetic/epigenetic analyses on patient biopsies and corresponding PDOX included array comparative genomic hybridization, transcriptional profiling, targeted sequencing and methylation arrays. Results: Using an efficient orthotopic xenografting procedure we obtain an overall tumor take-rate of close to 80%. We show that glioma PDOX retain the genetic and epigenetic profiles of primary patient biopsies throughout several generations of xenotransplantation. In particular they not only faithfully recapitulate gene amplification and expression of EGFR and EGFRvIII variant in a reproducible manner, also amplification and expression of rarer patient-specific EGFR variants is maintained. Overall genome-wide transcriptomic profiles of PDOXs remain very similar to patient biopsies and correlate better with the GBM cohort of TCGA (538 GBM samples) than conventional cell lines. Observed differences at the transcriptomic level are largely based on the replacement of human to mouse stromal cells, which impacts on the molecular sub-classification of GBM. Conclusion: We conclude that glioma PDOX models reflect patient heterogeneity and treatment response, and represent appropriate avatars for reproducible pre-clinical trials. Furthermore, by combining profiling of the somatic mutational landscape with large-scale drug screening, PDOX-derived tumor organoids can be applied to elucidate druggable targets and tumor response profiles in a personalized patient-specific manner.